A comparative study regarding the use of the tinted car in Malaysia and United Kingdom / Muhamad Amin Nasry Ahmad Salleh … [et al.] - Ahmad Salleh, Muhamad Amin Nasry; Alias, Muhammad Afiq; Jasmin, Mohamad Haris Syafiq; Sazali, Muhamad Izzad Emir (2014)
This research paper discuss on the issue of the tinted laws for vehicle and comparative study of regulation and enforcement of law regarding the rules of tinting vehicles window in Malaysia and the United Kingdom. In Malaysia the law that govern the instalment of tint films on car window is govern by the 2000 Amendment of the Motor Vehicle Rules while in United Kingdom, the legislature that being used in the Vehicle and Operator Services Agency under the Road Vehicles (Construction and Use) Regulations 1986.The main reason for this study is to study the relevancy of law in Malaysia that prohibit the tinting of the rear window. In the United Kingdom, there is no such restriction to that issue. The country of Malaysia are often has the same implementation of the law that is derived in the United Kingdom as most of the law comes from the United Kingdom due to both of them being a commonwealth countries so, the purpose is this paper is that the law of the rear part of the window should be the same as in the United Kingdom. For the implementation of law, in Malaysia, the enforcement is vague as there are many bodies that have the authority to enforce the law such as the Jabatan Pengangkutan Jalan (JPJ) and the police while in the United Kingdom, it is much easier as only the police has the power to enforce the law. The interview method was carried out and the outcome was noted in this paper. As conclusion, the respondent agreed that the prohibition of tinting the rear part was not relevant.